The Effect of Womens Leadership on Carbon Disclosure by the Top 100 Global Energy Leaders - Abd Majid N.; Jaaffar A.H. (MDPI, 2024)
The energy sector is one of the main sources of carbon emissions and the most significant global polluter. Womens concerns and the climate crisis were strongly associated when issues about climate change were first articulated in the United Nations Sustainable Development Goals stressing gender equality and climate mitigation actions have received very little attention in the last decade. Consequently, the primary issues raised by this study are the energy industry, and women and climate change. This study examined the effect of womens leadership on carbon disclosure among the top 100 global energy leaders from 2018 to 2020. This study unequivocally recognizes the effect of womens leadership as assessed by the number of female board members who are industry experts, serve as advisors, and pose as proxy community leaders for global energy leaders. This studys sample consisted of 291 observations of global energy leaders sourced from Thomson Reuters database. For the panel data analysis, STATA 14 (Version 14.) software was applied as the empirical methodology. The empirical findings showed that among the top energy leaders globally, women leaders increased the degree of carbon disclosure. The findings of this study provide novel insights into the importance of womens leadership in the energy sector for enhancing and promoting carbon disclosure. The validity of hypothesized links in the findings lends support to the resource dependence theory from the viewpoint of the energy leaders. This study also provides guidance for practitioners, governments, and policymakers on how to combat climate change, encourage the inclusion of as many women as feasible on boards, the promotion of gender parity, and support efforts to achieve the net zero carbon target. 2023 by the authors.